Analysis of Teacher's Feedback on Students in Writing Recount Text at Senior High School - Sari, Winda; Daulay, Sholihatul Hamidah (ENGLISH FRANCA : Academic Journal of English Language and Education, 2023)
This study aims to examine the types of written feedback given by teachers on the writing of eleventh-grade senior high school students at SMA Tarbiyah Islamiyah. The instrument used was document analysis to examine the type of written feedback given by the English teacher on the writing results of tenth-grade students majoring in Social Sciences (IPS) and Natural Sciences (IPA). The findings revealed that the two teachers used different written feedback on students' writing. Teachers who teach in the Science major tend to use direct written feedback and teachers who teach in the Social Sciences department use indirect feedback. It can be concluded that the reason for the different types of written feedback used is that teachers who teach in science majors think that direct feedback is more detailed and understood more quickly by students. Meanwhile, teachers who teach in the Social Sciences major argue that providing written feedback indirectly it can encourage students to think and make students more curious about the mistakes they write and students can ask questions to the teacher.